Major threats to a migratory raptor vary geographically along the eastern Mediterranean flyway. (October 2021) - Oppel, Steffen; Arkumarev, Volen; Bakari, Samuel; Dobrev, Vladimir; Saravia-Mullin, Victoria; Adefolu, Solomon; Sözüer, Lale Aktay; Apeverga, Paul T.; Arslan, Şafak; Barshep, Yahkat; Bino, Taulant; Bounas, Anastasios; et al.
Abstract: The Convention of Migratory Species aims to protect migratory animals throughout their range, but efficient mitigation of threats facing migratory birds is hindered by poor knowledge about the magnitude and geographic range of threats. We used an expert assessment to prioritise which threats to mitigate in 13 countries along the eastern Mediterranean flyway to protect globally threatened Egyptian Vultures Neophron percnopterus . We informed this assessment by satellite tracking 71 birds to quantify where and how mortalities occurred, surveying 4216 km of powerlines to detect carcasses, conducting 910 interviews to quantify poison use, and by surveying markets and hunters to assess direct persecution. Mortality of 50 birds occurred in Europe and the Mediterranean Sea (44%), the Middle East (18%), and Africa (38%), and mortality causes varied geographically. Inadvertent poisoning resulting from rural stakeholders targeting predators occurred along most of the flyway. On the breeding grounds in eastern Europe and in Saudi-Arabia, poisoning and collision and electrocution are the priority threats to mitigate. Electrocution on small and poorly designed electricity pylons was the priority threat in Turkey, Jordan, Egypt and Ethiopia. Direct persecution for belief-based use of vulture products was the priority threat in Nigeria and Niger, while other illegal killing was the priority threat in Lebanon and Syria. Our work cannot quantify which threat has the greatest demographic impact on Egyptian Vultures. Nonetheless, because all threats we assessed are relevant for many other migratory birds, our assessment highlights the priority threats that range states need to address to protect migratory birds.